2015
DOI: 10.1111/jopy.12187
|View full text |Cite
|
Sign up to set email alerts
|

Thin Images Reflected in the Water: Narcissism and Girls’ Vulnerability to the Thin‐Ideal

Abstract: The purpose of this research is to test how adolescent girls' narcissistic traits-characterized by a need to impress others and avoid ego-threat-influence acute adverse effects of thin-ideal exposure. Participants (11-15 years; total N = 366; all female) reported their narcissistic traits. Next, in two experiments, they viewed images of either very thin or average-sized models, reported their wishful identification with the models (Experiment 2), and tasted high-calorie foods in an alleged taste test (both exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Due to their charm, charisma, energy, approach-orientation, and willingness to step on others, they delve immediately into the deep, make speedy decisions, and take risks. They discount negative feedback (Campbell et al, 2000; Kernis & Sun, 1994), disengage self-protectively from threats to their self-image (Thomaes & Sedikides, 2016), are mentally tough (i.e., high on confidence, control, challenge, and commitment; Sabouri et al, 2016), 3 and are resilient declaring intentions to persist on challenging tasks even when they have encountered self-threat (e.g., negative feedback, disputation of their uniqueness; Nevicka, Baas, & Ten Velden, 2016) or persisting on impossible tasks provided these tasks are diagnostic of intelligence and no alternative routes to self-enhancement are available (Wallace, Ready, & Weitenhagen, 2009). Narcissistic leaders are not afraid to break barriers, dismantle prior structures, and build new ones all the while infusing the organization with excitement, enthusiasm, optimism, and purpose.…”
Section: Perturbationmentioning
confidence: 99%
“…Due to their charm, charisma, energy, approach-orientation, and willingness to step on others, they delve immediately into the deep, make speedy decisions, and take risks. They discount negative feedback (Campbell et al, 2000; Kernis & Sun, 1994), disengage self-protectively from threats to their self-image (Thomaes & Sedikides, 2016), are mentally tough (i.e., high on confidence, control, challenge, and commitment; Sabouri et al, 2016), 3 and are resilient declaring intentions to persist on challenging tasks even when they have encountered self-threat (e.g., negative feedback, disputation of their uniqueness; Nevicka, Baas, & Ten Velden, 2016) or persisting on impossible tasks provided these tasks are diagnostic of intelligence and no alternative routes to self-enhancement are available (Wallace, Ready, & Weitenhagen, 2009). Narcissistic leaders are not afraid to break barriers, dismantle prior structures, and build new ones all the while infusing the organization with excitement, enthusiasm, optimism, and purpose.…”
Section: Perturbationmentioning
confidence: 99%
“…And their overconfidence may hurt them: When betting on the correctness of their answers, they lose points (Campbell et al, ). Moreover, when they receive negative feedback, they blame others (Campbell, Reeder, Sedikides, & Elliot, ) or disengage from its consequences (Thomaes & Sedikides, ). Overall, then, narcissists are no more effective or competent than non‐narcissists in the agentic domain (Sedikides & Campbell, ), although this conclusion needs to be qualified; narcissists perform relatively well when they believe that winning a competition will reap them the benefits of acclaim (Wallace & Baumeister, ).…”
Section: Narcissismmentioning
confidence: 99%
“…Empirically, there is evidence that vulnerable (but not grandiose) narcissism in women is positively related to body shame (Carrotte & Anderson, 2019) and body dissatisfaction (Purton et al, 2018), whereas grandiose narcissistic women reported particularly positive body images (Jackson et al, 1992). Some studies have examined thinness-related concerns in particular (Brunton et al, 2005;Gordon & Dombeck, 2010;Maples et al, 2011;Swami et al, 2015;Thomaes & Sedikides, 2016), and the results have again varied as a function of the narcissism facet that was considered: Aspects allocable to vulnerable narcissism were positively related to drive for thinness; grandiose aspects had no or even protective effects on the degree of thinness concerns (for an overview, see also Bardone-Cone et al, 2020).…”
Section: The Relations Between Narcissism and Body Image Concernsmentioning
confidence: 99%
“…But who is especially vulnerable to these concerns? Previous research has investigated narcissism as one potential predictor but has yielded inconsistent results (e.g., Gordon & Dombeck, 2010;Thomaes & Sedikides, 2016). The present work readdresses the question of whether narcissism predicts body image concerns and extends previous work by (a) including both drive for thinness and drive for muscularity as key body image concerns, (b) incorporating insights regarding the tripartite structure of narcissism, including agentic, antagonistic, and neurotic aspects, (c) exploring the potential moderating and/or mediating roles of importance of appearance, and (d) applying latent modeling (i.e., structural equation modeling; SEM) across two independent samples to gain more robust insights.…”
Section: Introductionmentioning
confidence: 99%